2001
DOI: 10.1107/s0108768100014506
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic behaviour investigations and crystal structure of nitric acid dihydrate

Abstract: X-ray powder diffraction experiments are performed to prove the possible crystallization of nitric acid dihydrate (HNO(3).2H(2)O, further denoted NAD) and to determine the best thermal conditions for growing a single crystal. It is shown that the kinetic behaviour of NAD strongly depends on the preliminary thermal treatment. One good single crystal obtained by an in situ adapted Bridgman method procedure enabled determination of the crystal structure. The intensities of diffracted lines with h odd are all very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 11 publications
3
53
0
Order By: Relevance
“…Experimental studies using the X-ray diffraction or infrared spectroscopy have identified the nitric acid monohydrates (NAM) [10], nitric acid dihydrates (NAD) [11,12] and the nitric acid trihydrates (NAT) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies using the X-ray diffraction or infrared spectroscopy have identified the nitric acid monohydrates (NAM) [10], nitric acid dihydrates (NAD) [11,12] and the nitric acid trihydrates (NAT) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The results with two GGA parameterizations, namely, PBE and BLYP, show some small differences: the cell volume is increased by 2 % versus experiment with BLYP but reduced by almost the same amount with PBE, which overestimates the HB strength. Interlayer HB distances are underestimated in [13,14] [c] Previous DFT calculations performed with LCAO basis sets by Fernµndez-Torre et al [24] [d] Molecular dynamics simulations with plane-wave basis sets, performed by Walker et al [25] ChemPhysChem 2009, 10, 3229 -3238…”
Section: Geometry Optimizationmentioning
confidence: 99%
“…[18] X-ray diffraction investigations led to determination of two different modifications of NAD at ambient pressure, namely, the high-(b) and low-temperature (a) phases, both of which crystallize in the monoclinic system in space group P2 1 /n. [13,14] A high-pressure modification was recently found [25] but is not likely to exist under stratospheric conditions. In both crystals the molecules are arranged in layers that are approximately perpendicular to the c axis.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations